Electronic Transport Inhibiting of Carbon Nanotubes by 5f Elements. Issue 2 (15th January 2020) - Wang, Jia; Gong, Kui; Lu, Feifei; Xie, Weiyu; Zhu, Yu; Wang, Zhigang
Abstract: Based on the combination of the non‐equilibrium Green's function and density functional theory, a theoretical method for studying the transport behavior of high angular momentum 5f electrons is developed and the transport properties of the structure for actinide atoms embedded in carbon nanotubes (An@CNTs, An = Ac, Th, Pa and U) is reported. Results show that An@CNTs have lower transmission coefficients than that of CNTs. Furthermore, electrical bias to the U@(4, 4)/(5, 5) CNTs induces an additional transition spectral peak, which demonstrates that the U@(4, 4)/(5, 5) CNTs has a lower resistance. Therefore, 5f electrons of actinide atoms inhibit the electronic transport of CNTs. These findings may provide fresh insight into the transport properties of systems having higher angular momentum electrons. Abstract : A calculation method for quantum transport to study the transport properties of 5f‐electron systems using non‐equilibrium Green's function combined with density functional theory is developed. The transport properties of 5f electrons of actinide atoms show that they suppress electron transport.